Compositions of song Nakhon Champasri for creative research and music instruction in contemporary Isan Folk Music ensemble - Phulaiyaw, Akapong; Chuangprakhon, Sayam; Khamhongsa, Arthit (Research Journal in Advanced Humanities, 2023)
The compositions of "Nakhon Champasri" for a contemporary Isan folk music ensemble, focusing on creative music and music instruction in a contemporary Isan style The objective of this was to produce academic works that advance the understanding of creative music and contribute to broader research in music, the arts, and culture. Using a creative research approach, incorporating traditional Thai Isan folk melodies and infusing them with intriguing patterns, rhythmic rise, Western harmonies, and chords, such as random notations, block chords, pentatonic scales, passing notes, rhythmic patterns, ostinato, improvisation, and passing notes, while utilizing harmonies of different voice counts The findings showcase the successful integration of traditional Isan folk melodies with contemporary compositional techniques, resulting in captivating and harmonically rich compositions. The practical implications of its value as a teaching tool for students pursuing a Bachelor of Music degree, allowing them to explore and learn about contemporary Isan folk music composition, These compositions offer opportunities for musicians and music enthusiasts interested in general music composition to engage with and appreciate the unique genre of contemporary Isan folk music. contributing to the advancement of creative music and serving as valuable resources for music instruction.